PENGARUH METODE CARD SOFT TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN AL-QUR'AN HADIST KELAS 7 DI MTS NUSANTARA KOTA PROBOLINGGO - M Mahbubi; Agustin Nur Fadillah (LPPM STAI Muhammadiyah Probolinggo, 2025)
The compiler of this work in order to analyze in detail in order to implement the card method is reviewed from the motivational aspect of the Al-Quran Hadith material located in the archipelago of Probolinggo city, precisely class 7. Qualitative as a reference in processing data in the preparation of this work. The process is through pretest and post-test experiments on one group. From the results of the test, the data is then taken to the next step, namely SPSS processing. The results of this work show that there is an increase in motivation that can be seen from this process through the card method. The value obtained is 84.12 for the pretest and 86.88 for the post-test. With these two differences in value, it is clear that by using the Cut method there are satisfactory results from the motivational aspect and it can be concluded that the Cut short method is effective in increasing student learning motivation because it creates a more interactive and enjoyable learning atmosphere